"Between Two Communities So Diverse": Confrontation and Collaboration in Cuba, 1898–1902. Issue 1 (2nd January 2017) - Gonzalez, Joseph J.
ABSTRACT: In 1898, the United States government took possession of Cuba. Rather than annexation, the William McKinley Administration chose to create a new nation-state. Cuba's fate therefore was unlike that of the Philippines, waiting until after the Second World War for independence. It leads to a question: when it came to Cuba, why the choice of creating a nation rather than annexation? The short answer is that the Cubans would have resisted annexation by force. The longer—and more interesting—answer is that annexation became unnecessary: Over time, Cuba's nationalist elite proved willing to co-operate with American interests, and McKinley's Administration left Cuba in nationalist hands, provided those hands were bound by the Platt Amendment. Historians have argued that Cuban nationalists co-operated because of coercion. Whilst true, Cuba's nationalists also saw value in a relationship with the United States. Therefore, Cuba's new leaders resisted American demands in ways not only to preserve the good opinion of Washington, but to prove themselves capable of civilised self-government.